Anatomy of dissent in Islamic societies ibadism, rebellion, and legitimacy - Souaiaia, Ahmed E.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
Anatomy of Dissent in Islam is an interdisciplinary study of political and legal dissent in Islamic civilization from the seventh century on. (7th century). Using Ibadism as a case study, this work explores the events and teachings that shaped legitimacy and rebellion, orthodoxy and sectarianism, and law and culture in Islamic societies.
Keywords: Social sciences; Islam; Religion -- History; Religion and sociology; Middle East -- History; Social Sciences; Sociology of Religion; History of Religion; History of the Middle East; Islam; Social Aspects of Religion